2019
DOI: 10.1016/j.nicl.2018.101629
|View full text |Cite
|
Sign up to set email alerts
|

Changes in default mode network connectivity in different glucose metabolism status and diabetes duration

Abstract: Aims/hypothesesIt is now generally accepted that diabetes increases the risk for cognitive impairment, but the precise mechanisms are poorly understood. In recent years, resting-state functional magnetic resonance imaging (rs-fMRI) is increasingly used to investigate the neural basis of cognitive dysfunction in type 2 diabetes (T2D) patients. Alterations in brain functional connectivity may underlie diabetes-related cognitive dysfunction and brain damage. The aim of this study was to investigate the changes in… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

7
32
0
4

Year Published

2019
2019
2024
2024

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 34 publications
(43 citation statements)
references
References 33 publications
(39 reference statements)
7
32
0
4
Order By: Relevance
“…The disruption of CB in T2DM is thus not unexpected, which might reflect an overlapping pattern during the process of cognitive decline. Besides, we and several other studies have previously reported DMN disconnection in T2DM patients, especially in its posterior components (Cui et al, 2015;Ishibashi et al, 2018;Liu et al, 2019). Given that CB is the anatomical basis for DMN (van den Heuvel et al, 2008), the present CB abnormalities not only are supported by the previous functional results but also extend fMRI studies by adding anatomical evidence.…”
Section: Discussionsupporting
confidence: 88%
“…The disruption of CB in T2DM is thus not unexpected, which might reflect an overlapping pattern during the process of cognitive decline. Besides, we and several other studies have previously reported DMN disconnection in T2DM patients, especially in its posterior components (Cui et al, 2015;Ishibashi et al, 2018;Liu et al, 2019). Given that CB is the anatomical basis for DMN (van den Heuvel et al, 2008), the present CB abnormalities not only are supported by the previous functional results but also extend fMRI studies by adding anatomical evidence.…”
Section: Discussionsupporting
confidence: 88%
“…coupling in DMN found in our study is consistent with the findings in previous studies that CBF and DMN connectivity were altered in individuals with disrupted systemic metabolism [57][58][59][60][61][62][63][64].…”
Section: Plos Onesupporting
confidence: 93%
“…bER which showed the strongest correlation with CHF is therefore expected to interact more with DMN. The bER-DMN coupling is consistent with findings in previous studies that CBF and DMN connectivity were altered in individuals with disrupted systemic metabolism (Chen et al, 2017;Ishibashi et al, 2018;Ishibashi et al, 2016;Li et al, 2017;Liu et al, 2017a;Liu et al, 2019;Lockwood et al, 1991;Qi et al, 2014).…”
Section: Default Mode Networksupporting
confidence: 91%